2004
DOI: 10.1182/blood-2003-05-1685
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo effects of tPA and PAI-1 on blood vessel tone

Abstract: Tissue type plasminogen activator (tPA) is a key enzyme in the fibrinolytic cascade. In this paper we report that tPA contains 2 independent epitopes that exert opposite effects on blood vessel tone. Low concentrations of tPA (1 nM) inhibit the phenylephrine (PE)-induced contraction of isolated aorta rings. In contrast, higher concentrations (20 nM) stimulate the contractile effect of PE. The 2 putative vasoactive epitopes of tPA are regulated by the plasminogen activator inhibitor-1 (PAI-1) and by a PAI-1-der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
119
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(127 citation statements)
references
References 29 publications
6
119
2
Order By: Relevance
“…This outcome suggests that the vasorelaxation induced by high concentrations of uPA is mediated through a process that does not require LRP-1 or a related family member. This is similar to our previous finding that the vasoactive effect induced by high concentrations of tPA (20 nM) is independent of LRP (30).…”
Section: Role Of Lrp and Upa Catalytic Activitysupporting
confidence: 82%
See 1 more Smart Citation
“…This outcome suggests that the vasorelaxation induced by high concentrations of uPA is mediated through a process that does not require LRP-1 or a related family member. This is similar to our previous finding that the vasoactive effect induced by high concentrations of tPA (20 nM) is independent of LRP (30).…”
Section: Role Of Lrp and Upa Catalytic Activitysupporting
confidence: 82%
“…We previously observed that the stimulatory, but not inhibitory, effects of tPA on the contraction of isolated aortic rings were LRP-dependent (30). Therefore, we examined the involvement of this receptor in uPA-induced alterations in pulmonary arterial contractility.…”
Section: Role Of Lrp and Upa Catalytic Activitymentioning
confidence: 99%
“…MK-801 blocks the neurotoxic effects of tPA by blocking the receptor, thereby inhibiting calcium overload. Recently, it has been shown that tPA can have complex vasoactive roles in brain; at low 1 nM concentrations tPA inhibits phenylephrine-induced vasoconstriction, whereas at high 20 nM concentrations tPA augmented phenylephrine's effects on vessel tone (Nasser et al, 2004).…”
Section: Tpa Neurotoxicity Via Nmda Receptorsmentioning
confidence: 99%
“…22 WT-tPA (50 nM) or WT-uPA (5 nM) was incubated with plasminogen (500 nM) and the chromogenic substrate of plasmin S-2251 (Innovative Research, Novi, MI) (100 mM) alone or in the presence of tPA-S 481 A (100 nM) or tranexamic acid (1 mM). Generation of plasmin was assessed by change in optical density (OD) at 405 nm.…”
Section: Chromogenic Assay Of Plasminogen Activationmentioning
confidence: 99%
“…Plasminogen activators (PAs) play important roles in neurotransmission, [17][18][19] postinjury neuronal apoptosis, 20,21 and regulation of cerebrovascular reactivity, 15,16,22 but their contributions to ICH have received less attention. We hypothesized that a rapid, protracted, and striking increase in the local concentration of endogenous PAs is primarily responsible for exuberant local fibrinolysis at sites of trauma, leading to premature clot lysis and expansion of ICH.…”
Section: Introductionmentioning
confidence: 99%